2021
DOI: 10.1088/1755-1315/807/2/022041
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of cellulolytic fungi at rhizosphere of safira taro plant

Abstract: Agriculture waste and pathogen cell wall of plant contain a lot of cellulose which are very difficult to degrade. One of the ways to hydrolyse them is through utilizing cellulase, an enzyme produced from secondary metabolite of cellulolytic fungi. This research was aimed at isolating fungi from rhizosphere of safira taro plant and testing the isolate capability to produce cellulase enzyme to be able to act as decomposer and biocontrol of the plant. The research methods are isolating rhizosphere fungi, testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Sun et al [19] found that the relative enzyme activity index ranged from 1.89 to 3.19. Wisdawati et al [20] reported ICMC index ranging from 0 to 1.66. Similarly, Gat et al [21] obtained ICMC values ranging from 0 to 0.56.…”
Section: Relative Enzyme Activitymentioning
confidence: 99%
“…Sun et al [19] found that the relative enzyme activity index ranged from 1.89 to 3.19. Wisdawati et al [20] reported ICMC index ranging from 0 to 1.66. Similarly, Gat et al [21] obtained ICMC values ranging from 0 to 0.56.…”
Section: Relative Enzyme Activitymentioning
confidence: 99%